Правовий захист комп’ютерних програм - Біленчук, П.; Bilenchuk, P.; Борисова, Л.; Borysova, L. (Волинський національний університет імені Лесі Українки, 2017)
Як продукт інтелектуальної діяльності людини, комп'ютерні програми потребують правового захисту від незаконного привласнення без дозволу осіб, які мають на них охоронні документи. Виникнення правових колізій при захисті комп'ютерних програм свідчить, що існуючого регулювання авторським правом недостатньо. Використання комп'ютерної програми без дозволу автора, невиконання умов договору є порушенням авторських прав і може бути підставою для притягнення порушника до юридичної відповідальності: цивільно-правової (ст. 431 Цивільного кодексу, ст. 52 Закону України « Про авторське право і суміжні права»); адміністративної (ст. 51-2 Кодексу про адміністративні правопорушення); кримінальної (ст. 176 Кримінального кодексу України). The computer software occupies a special place among intellectual property objects since it is not only a foundation for scientific and technical development, but also a commodity. Like any other product of human intellectual activity, computer programs require legal protection from illegal appropriation without the permission of a person who has the copyright protection documents. The emergence of legal collisions in the protection of computer programs indicates that existing protection of software copyright is not sufficient. In Ukraine, as inmany other countries, legislation defines computer programs as the objects protected by copyright. The copyright of a computer program is regarded as such that results from the very fact of its creation and does notrequire registration or special documentation (Art. 437 Civil Code of Ukraine). The author emphasizes that initial and primary legal subject, who owns the copyright, is the creator of a computer program. In addition, copyright may be owned by other individuals and entities who have acquired the rights to a computer program under contract or law. Using a computer program without a permit (license) of the author or failure to comply with the contract terms is regarded as copyright infringement and may be a ground for bringing a person-violator to the court according to followingtypes of liability under the current legislation of Ukraine: civil-legal (property liability) –Art.431 of the Civil Code and Art.52 of the Law of Ukraine «On Copyright and Related Rights»; administrative – art.51-2 of the Code on Administrative Offenses; or criminal – art.176 of the Criminal Code of Ukraine.
Legal Protection of the Computer Programs
Keywords: інтелектуальна власність; авторське право; комп'ютерна програма; правовий захист; юридична відповідальність; intellectual property; copyright; computer software; legal protection; legal liability